2012
DOI: 10.3136/nskkk.59.394
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Release-Suppressive Effect of Water Extracts Prepared from Flower and Leaf of Chrysanthemum, Shiranui Himekiku

Abstract: To clarify the immunoregulatory activity of the chrysanthemum plant Shiranui himekiku, the effects of its flower and leaf extracts on proliferation and histamine release of rat and human basophilic leukemia cells were examined. Water extracts of flower and leaf suppressed proliferation and histamine release of rat RBL-2H3 cells dose-dependently at concentrations over 10 µg/mL. The histamine release-suppressive effect of the leaf extract was as strong as that of the flower extract. The effects of these extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Interestingly, CE extracts made from plant petals reportedly suppress proliferation of various cancer lines . Moreover, relevant to immune responses, CE extracts suppress histamine release from the basophil cell line RBL‐2H3 . Mechanisms underlying these effects are unknown, but based on our findings, future analysis should address whether any of these outcomes are due to ANGPTL2 inhibition.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, CE extracts made from plant petals reportedly suppress proliferation of various cancer lines . Moreover, relevant to immune responses, CE extracts suppress histamine release from the basophil cell line RBL‐2H3 . Mechanisms underlying these effects are unknown, but based on our findings, future analysis should address whether any of these outcomes are due to ANGPTL2 inhibition.…”
Section: Discussionmentioning
confidence: 81%
“…are listed in the Japanese Pharmacopoeia [ 3 ]. Many studies have investigated the therapeutic potential of these flowers as antioxidant [ 4 ], anti-inflammatory [ 5 ], hepatoprotective [ 6 ], antidiabetic [ 7 ], neuroprotective [ 8 ], tyrosinase inhibitory [ 9 ], and anti-allergic agents [ 10 ]. These activities were attributed to the abundance of polyphenols and flavonoids [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the leaves of Chrysanthemum species, previous studies have reported that Chrysanthemum leaves exhibit histamine release inhibition [ 10 ], antimicrobial, anti-inflammatory, and antioxidant activities [ 23 , 24 , 25 ]. Recently, C. morifolium leaves were reported to contain chlorogenic acid, 3,5-dicaffeoylquinic acid, luteoloside, and quercetin [ 26 ].…”
Section: Introductionmentioning
confidence: 99%